تأثير استخدام الوسائط السّمعيّة والبصريّة في إتقان المفردات العربيّة - Nur - Hasnah; Afrina Refdianti; Rita Febrianta; Mohamed Daud Mohamed Daud (UNiversitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The research is motivated by the low mastery of Arabic language mufradat by Islamic Religious Education (PAI) students at UIN Sjech M. Djamil Djambek Bukittinggi. Meanwhile، mufradat is very influential on students' proficiency in Arabic because mufradat is one of the components of Arabic. PAI students are required to understand Arabic because there are many courses whose reference books use Arabic such as Qawaid Imla '، Educational Manuscript Studies، Tahsin Al-Qur'an، Arabic Calligraphy، Fiqh Muamalat، etc. This study aims to determine the effect of audio-visual media on the mastery of mufradat of PAI students. This type of research is quantitative research with a quasi-experimental design method. Data were taken from the results of the pre test and post test in the control and experimental classes. After the data was processed using SPSS، the data obtained were not normally distributed. Therefore، to test the hypothesis، a nonparametric test was carried out، namely the Wilcoxon test. From the results of this test، it can be obtained a significance of 0.000 which is small from 0.05 with an error level of 5%، so according to the basis for decision making in the Wilcoxon test it can be say that Ha is accepted، that is، there is a significant effect of using audio-visual media on the mastery of mufradat of PAI students.